Porous Properties of Silica Prepared by Selective Acid Leaching of Heat-Treated Vermiculite - Jadambaa, Temuujin; Minjigmaa, A.; Jadambaa, T.; Tsend-Ayush, S.; MacKenzie, K. (Izdatel'stvo Sibirskogo Otdeleniya Rossiiskoi Akademii Nauk, 2008)
The porous properties of silica prepared from heat-treated Transvaal vermiculite (South Africa) by acid leaching were determined. The effect of temperature on the destruction of the crystal structure of the vermiculite was determined, leading to the adoption of heating conditions of 600 o C for 2 h which produce a fully amorphous sample. The heat-treated samples were leached with 2M hydrochloric acid at 80 o C for 0.5, 2 and 8 h and their porous properties were characterized by measuring their specific surface areas and pore volumes. The highest surface area and pore volume (559 m2/g and 0.51 ml/g) was obtained for the sample leached for 8 h. Thermal amorphisation of vermiculite exerts a negative influence on the porous properties of the mineral.